Médecines créoles guyanaise et haïtienne face au Covid-19 - Marc-Alexandre Tareau; Guillaume Odonne (Revue d'ethnoécologie, 2023)
In the context of the Covid-19 pandemic, the use of medicinal plants to prevent, cure, and combat the symptoms of Covid-19 has prevailed among the Guyanese and Haitian Creole communities in French Guiana. Quassia amara was the most frequently used medicinal plant by the French Guianese Creole community, while Momordica charantia was the most mentioned species by Haitian Creoles. The preeminent use of bitter plants, in prevention as well as in curative therapy, is in line with the traditional theory of Creole medicine, which perceives fever as the result of « dirty blood » that only the bitterness of the plants would allow to cure effectively.In Creole nosologies, Covid-19 falls into the macro-category of « fever diseases ». Indeed, on the basis of a symptomatological analogy, this disease was quickly assimilated in these systems to other pathologies causing high fevers. The respiratory symptoms are also perceived as qualifying, mobilizing many species traditionally used to treat these pathologies. Finally, to a lesser extent, and especially among the most religious, Covid-19 is a « devil's disease », mainly because of the global disruption it has caused. The first two interpretations, as well as the remedies used, are part of a broader search for balance between « hot » and « cold » states, which is very present in Creole medicines throughout the American continent.A distrust of health institutions and the messages they disseminate has been clearly expressed, leading to a withdrawal into identity through transnational (digital) networks. Contrary to the usual pluralism, a strong cleavage between biomedicine and local herbal medicine was noted, and in particular a significant distrust of vaccines by the Creole population. This opposition has largely materialized in the form of a communitarianism of « them » against « us », « their vaccine » against « our plants ». This faith in plants, in prevention as well as in care, while the risks linked to disease are minimized, while the side effects of vaccines are exaggerated, is very much relayed by certain social networks. One of the explanations may be this perception of the non-newness of the disease taken as a set of already understood symptoms, as well as the strong preventive valence of Creole phytotherapies.